SIPOU (Siphonosoma australe-australe): PEMANFAATANNYA SEBAGAI BAHAN PANGAN - Fatimah, Shalawatun Amaliah; Asnani, Asnani; Suwarjoyowirayatno, Suwarjoyowirayatno (Jurnal Fish Protech, 2021)
ABSTRACT         Sipou (Siphonosoma australe-australe) or sipuncula (peanut worm) is a marine animal that can be found in the coastal areas of Toronipa, Konawe Regency, Southeast Sulawesi. Sipou has been used as food and traditional medicine. It has been researched that it has a complete nutritional content, traditionally used as a nutraceutical ingredient against tuberculosis, regulates the function of the stomach and spleen, and restores health caused by pathogens. Due to its broad benefits, Sipou is now known to have an anti-inflammatory, anti-diabetic, or antihyperglycemic function in what has been done on its extracts. Indonesia is a region that holds a wealth of various types of marine animals, one of which is sipou, which until now is still very rarely used, even the processing technology is new in the form of dry raw materials and used as food ingredients. Meanwhile, sipou research as a medicinal ingredient is still limited and Sipou products are still exported as dry whole raw materials to Asian countries. Given its potential resources, research towards industry, processing, pharmaceuticals, and health needs to be increased. The research is intended to further introduce and support various industries in increasing the added value of processing and processed Sipou which is very useful. Keywords: Foodstuffs, Sipou, processing techniquesABSTRAKSipou (Siphonosoma australe-australe) atau sipuncula (peanut worm) merupakan hewan laut yang dapat ditemui di wilayah pesisir pantai Toronipa, Kabupaten Konawe, Sulawesi Tenggara. Sipou telah dimanfaatkan sebagai bahan pangan dan pengobatan tradisional. Telah diteliti memiliki kandungan nutrisi yang lengkap, secara tradisional telah dimanfaatkan sebagai bahan nutraceutical terhadap penyakit tuberkulosis, pengatur fungsi lambung dan limpa, serta pemulihan kesehatan yang disebabkan oleh patogen. Karena manfaatnya yang cukup luas, kini sipou diketahui memiliki fungsi sebagai antiinflamasi, anti diabetes atau antihiperglikemik dalam penetian yang telah dilakukan terhadap ektraknya. Indonesia merupakan wilayah yang menyimpan kekayaan berbagai jenis hewan laut, salah satunya adalah sipou yang hingga saat ini pemanfaatannya masih sangat jarang bahkan teknologi pengolahannya baru dalam bentuk bahan baku kering dan dimanfaatkan sebagai bahan pangan. Sementara penelitian sipou  sebagai bahan obat masih terbatas dan produk sipou masih diekspor dalam bentuk bahan baku utuh kering ke negara-negara Asia. Mengingat sumberdayanya yang cukup potensial, maka penelitian ke arah bidang industri, pengolahan, farmasi dan kesehatan perlu ditingkatkan. Penelitian tersebut untuk lebih memperkenalkan dan mendukung berbagai industri dalam peningkatan nilai tambah dari pengolahan dan hasil olahan sipou yang sangat bermanfaat.Kata kunci: Bahan pangan, Sipou, teknik pengolahan